Comparative study for microcystin-LR sorption onto biochars produced from various plant- and animal-wastes at different pyrolysis temperatures: Influencing mechanisms of biochar properties. (January 2018) - Li, Jieming; Cao, Linrong; Yuan, Yue; Wang, Ruiping; Wen, Yunze; Man, Jiyong
Highlights: Biochars produced from various materials at different temperatures were characterized. Microcystin-LR sorption ability varied as a function of biochar structural properties. At the same production temperature chicken manure biochars showed the best sorption. High ash content might be important for enhancing microcystin-LR sorption by biochars. Chicken manure biochars were the most efficient sorbents to remove microcystin-LR. Abstract: Diverse biochars produced from various feedstock sources (i.e., plant- and animal-wastes) at different pyrolysis temperatures (PTs) were characterized for their structural properties and sorption behaviors of aqueous microcystin-LR (MC-LR). Results indicated that MC-LR sorption capability of tested biochars varied as a function of biochar structural properties. Sorption mechanisms involved electrostatic attraction, pore-filling, hydrogen-bonding effect and π-π electron donor-acceptor interaction, but predominant mechanisms varied for different biochars. At the same PT (300 or 600 °C), chicken manure-derived biochars (CMBs) exhibited stronger MC-LR sorption than others, with sorption coefficient ( K d ) of 6.321–15.529 L g −1 and 6.354–8.294 L g −1 at aqueous equilibrium concentration ( C e ) of 40 and 200 μg L −1, respectively. Higher mesoporosity, the point of zero charge and total surface groups concentration related to higher ash content of CMBs, which might be indispensable for enhancing MC-LR sorption. This study suggested that CMBs have great potential as low-cost sustainable sorbents to abate MC-LR contamination.